Evaluasi Kecernaan In Vitro Bahan Kering, Bahan Organik dan Protein Kasar Penggunaan Kulit Buah Jagung Amoniasi dalam Ransum Ternak Sapi - Jul Andayani (Fakultas Peternakan Universitas Jambi, 2010)
An experiment was conducted to evaluate ammoniated corn husk in vitro digestibility in cattle ration. Measured parameters in the current experiment were in vitro digestibility of dry matter, organic matter, crude protein. This study was assigned into completely randomized design (CRD) with 5 treatments and 4 replications. The treatments were ; T0 = 70% Forage (100% grass + 0% ammoniation of Corn husk) + 30 % Concentrate, T1 = 70% Forage (75 % grass + 25% ammoniation of Corn husk) + 30 % Concentrate, T2 = 70% Forage (50% grass + 50% ammoniation of Corn husk) + 30 % Concentrate, T3 = 70% Forage (25% grass + 75% ammoniation of Corn husk) + 30 % Concentrate, T4 = 70% Forage (0% grass + 100% ammoniation of Corn husk) + 30 % Concentrate. Result of this study showed that the treatments were significantly (P<0,05) influence digestibility of dry matter, organic matter and crude protein. Increased level of ammoniated corned corn husk made higher in vitro digestibility of ration. It concluded that ammoniation of corn husk could increase digestibility and th eammoniated corn husk may substitute forage in cattle ration.